Stress as a social tool that limits the freedom of the individual. Review of Peter Sloterdijk’s book "Stres a wolność". Trans. into Polish by B. Baran, Warszawa, Wydawnictwo Aletheia, 2018. - Janicka, Joanna Ilona (Folia Philosophica, 2019)
In the reviewed text entitled Stres a wolność (Stress and Freedom) Peter Sloterdijk argues that society by means of stress regulates the area of the freedom of individuals. The review presents the content, discusses the form and assesses the scope of the issue.